Pengaruh Budaya Organisasi dan Employee Engagement Terhadap Turnover Intention Pada Perusahaan Startup - Muhammad Andi; Mawardi Mawardi; Kasmaniar Kasmaniar; Saiful Amri; Maksalmina Maksalmina (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine how organizational culture and the level of employee engagement influence employees' turnover intentions within startup companies. High employee turnover in the startup sector which can lead to financial and operational issues served as the primary motivation for this research. A quantitative approach with a causal-correlational design was employed. The study population consisted of 220 active employees, with the sample size determined using Slovin's formula at a 5% margin of error. Data were collected via questionnaires and analyzed using multiple linear regression. The results indicate that organizational culture has a positive and significant partial effect on turnover intention (t-calculated 6.597 > t-table 1.975). Similarly, employee engagement has a positive and significant effect on turnover intention (t-calculated 3.988 > t-table 1.975). Collectively, both independent variables significantly influence employees' turnover intentions (F-calculated 29.017). These findings demonstrate that the management of work culture and emotional connections among employees is crucial in reducing the number of staff members who decide to leave a startup.